FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN PRAKTIK PENCEGAHAN DEMAM BERDARAH DENGUE (DBD) OLEH IBU RUMAH TANGGA DI KELURAHAN DOPLANG, PURWOREJO - Maria Ratih Widiyaning; Syamsulhadi Budi Musthofa; Bagoes Widjanarko (Jurnal Kesehatan Masyarakat (Undip), 2018)
Dengue Hemorrhagic Fever (DHF) is a viral disease caused by DEN-1, DEN-1, DEN-3, or DEN-4, which is transmitted through the bite of mosquitoes of Aedes aegypti and Aedes albopictus. Puskesmas Mranti have the most number of cases with total 49 cases, most cases occur in Doplang Village with total 14 cases. The purpose of this research is to know the factors that related to the prevention practice of DHF in Doplang Village, Purworejo. This research is a descriptive analytic research with cross sectional design. Total population on this research are 1157 househols, with 89 samples. Data analysis used on this research is univariate and bivariat analysis with Chi Square test (the significance level= 0.05). The majority of respondents are in the advanced adult category (57.3%), the most level of education is graduated from university (41.6%), the majority of respondents working as civil servants (39.3%). Respondents with good knowledge (58.4%), positive attitude (52.8%), available of information facilities (55.1%), easy access to information (73.0%), Puskesmas officer’s support (65.2%), health cadres’ support (55.1%), family’s support (66.3%), and neighbors’ support (61.8%). The Chi Square test results showed there is a correlation between educational level of respondents (p = 0.000), the attitude of respondents (p = 0.000), the Puskesmas officer support (p = 0.004), cadre support (p = 0.001), family support (p = 0.000), and neighbors support (p = 0.000) with the prevention practice of DHF. There is no correlation between the age of respondents, occupation, knowledge, availability of information facilities, and easy access to information on DHF prevention practice.